Peptides and Peptidomimetics as Potential Antiobesity Agents: Overview of Current Status - Kumar, Maushmi S. (Frontiers in Nutrition, 2019)
There is a high occurrence of obesity worldwide without many new medications being approved for its treatment. Therefore, there is an urgent need to introduce new approaches for treating obesity. Bioactive peptides have been used to treat metabolic disorders- such as type-2 diabetes and obesity; while also possessing anti-oxidant, anti-inflammatory, anti-microbial, and anti-viral properties. However, the development of these peptides has taken backstage due to their size, reduced stability, poor delivery and bioavailability, fast rate of degradation etc. But with the emergence of newer techniques for multifunctional peptides, mimetics, peptide analogs, and aptamers, there is a sudden revival in this therapeutic field. An increased attention is required for development of the natural peptides from food and marine sources which can mimic the function of mediators involved in weight management to avoid obesity. Herein, the search for the structures of anti-obesity peptides was carried out in order to establish their potential for drug development in future. An extensive search for the current status of endogenous, food and marine peptides, with reference to novel and interesting experimental approaches based on peptidomimetics for controlling obesity, was performed. Apolipoprotein A-I (apoA-I), melanocortin-4 receptor (MC4R)-specific agonist, GLP-1 dual and triple agonists, neuropeptides and prolactin-releasing peptide mimetics were specifically examined for their anti-obesity role. Novel peptides, mimetics, and synthesis interventions are transpiring and might offer safer alternatives for otherwise scarcely available safe antiobesity drug. A deeper understanding of peptides and their chemistry through the use of peptide engineering can be useful to overcome the disadvantages and select best mimetics and analogs for treatment in future.